Manejement Fisioterapi Pada Lansia Dengan Gangguan Keseimbangan dan Resiko Jatuh di Puskesmas Kaligawe Semarang - Aril Naila; Aisyah Salsabilla; Bernadeta Titis; Dicky Setya; Dina Nur; Johanna Roulita; Nabila Putri Adiba; Restu Tama Febriany; Movita Nur Peristiwaningrum (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
The elderly are an age group that is prone to experiencing balance disorders due to degenerative processes, decreased muscle strength, and sensorimotor system disorders. These conditions increase the risk of falling, which can have an impact on limited functional activities and a decrease in quality of life. The Kaligawe Semarang Health Center has an elderly community with the last number in 2025 as many as 30 people who are targeted in the promotive and preventive physiotherapy programs related to fall prevention. This activity aims to increase the understanding of the elderly about the importance of balance exercises as well as provide education and demonstrations of simple exercises that can be done independently to reduce the risk of falling. The methods used are in the form of counseling, distribution of educational media, and direct practice of balance exercises. The physiotherapy management program in the elderly community of the Kaligawe Health Center has succeeded in improving the understanding and skills of the elderly in maintaining balance and reducing the risk of falling. The sustainability of the program through regular exercises at home is expected to support the independence and quality of life of the elderly.